Endometriosis Umbilikal Primer: Laporan Kasus - Kalesaran, Laurens; Torar, Ridel (Universitas Sam Ratulangi, 2025)
Abstract: Primary umbilical endometriosis (PUE) is characterized by the presence of endometrial tissue in the umbilicus without a prior history of surgery, often accompanied by cyclical bleeding corresponding to the menstrual cycle. We reported a 41-year-old woman presented with cyclical bleeding from the umbilicus, coinciding with her menstrual periods for several months. Physical examination revealed a small, firm nodule with blood secretion at the umbilicus. The patient had no history of abdominal trauma or previous surgery. Abdominal ultrasonography suggested a diagnosis of umbilical endometriosis. The patient underwent total excision of the umbilical nodule, and histopathological examination confirmed the presence of endometrial tissue. This PUE should be considered as a differential diagnosis in reproductive-age women presenting with umbilical bleeding associated with the menstrual cycle. In this case, the absence of surgical history made the diagnosis of PUE more evident. Surgical treatment with total excision is the main therapeutic option to prevent recurrence. Post-excision histopathological examination is crucial to confirm the diagnosis. This study highlights the importance of clinical awareness of this rare condition to ensure early diagnosis. In conclusion, PUE is a rare condition that should be suspected in patients with the characteristic symptom of cyclical umbilical bleeding. Surgical excision with histopathological confirmation is the standard treatment, with a good prognosis and minimal risk of recurrence. Keywords: primary umbilical endometriosis; umbilical bleeding; surgical excision Abstrak: Endometriosis umbilikalis primer (EUP) ditandai dengan adanya jaringan endometrium di umbilikus tanpa riwayat operasi sebelumnya, yang sering disertai perdarahan siklik sesuai dengan siklus menstruasi. Kami melaporkan kasus seorang wanita berusia 41 tahun dengan keluhan perdarahan siklik dari umbilikus yang selalu bertepatan dengan periode menstruasinya selama beberapa bulan terakhir. Pemeriksaan fisik menunjukkan adanya nodul kecil dan keras dengan sekresi darah di umbilikus. Pasien tidak memiliki riwayat trauma abdomen atau operasi sebelumnya. Pemeriksaan ultrasonografi abdomen mengarahkan kepada diagnosis endometriosis umbilikalis. Pasien menjalani eksisi total nodul umbilikalis, dan hasil histopatologik mengonfirmasi adanya jaringan endometrium. EUP harus dipertimbangkan sebagai diagnosis banding pada wanita usia reproduktif dengan keluhan perdarahan umbilikalis yang berhubungan dengan siklus menstruasi. Pada kasus ini, tidak adanya riwayat operasi menjadikan diagnosis EUP lebih jelas. Pembedahan berupa eksisi total merupakan pilihan terapi utama untuk menghindari kekambuhan. Pemeriksaan histopatologik pasca-eksisi sangat penting untuk memastikan diagnosis. Studi ini menekankan pentingnya kesadaran klinis terhadap kondisi langka ini agar diagnosis dapat ditegakkan lebih dini. Simpulan studi ini ialah endometriosis umbilikalis primer merupakan kondisi langka yang penting untuk diwaspadai pada pasien dengan gejala khas berupa perdarahan umbilikalis yang siklik. Eksisi bedah dengan konfirmasi histopatologi menjadi standar penanganan utama, dengan hasil prognosis yang baik dan risiko kekambuhan minimal. Kata kunci: endometriosis umbilikalis primer; perdarahan umbilikus; eksisi bedah